The Importance of Studying Infectious and Parasitic Diseases of Wild Animals in the Amazon Biome with a Focus on One Health - Felipe Masiero Salvarani; Hanna Gabriela da Silva Oliveira; Letícia Yasmin Silva Correa; Aline Alessandra Lima Soares; Brenda Cabral Ferreira (Veterinary Sciences)
The Amazon Biome is home to an extraordinary diversity of wildlife, many of which are reservoirs or vectors for infectious and parasitic diseases that can impact not only the health of wild animals but also human and domestic animal populations. This narrative review highlights the critical importance of studying infectious and parasitic diseases in wild animals within the Amazon, particularly in the context of the One Health approach, which recognizes the interconnectedness of human, animal, and environmental health. This narrative review examines key pathogens, including viruses, bacteria, and parasites, that pose significant risks to wildlife conservation and public health. Through a synthesis of recent literature, this article emphasizes the need for comprehensive surveillance, research, and collaboration between the veterinary, medical, and environmental sectors. The results underscore the urgent necessity for an integrated response to emerging diseases, particularly as environmental changes and human activities increasingly disrupt ecosystems in the region. The conclusions advocate for the reinforcement of One Health initiatives in the Amazon Biome to ensure the protection of biodiversity and the prevention of zoonotic disease transmission to human populations.